ЎРТА АСРЛАРДА ХОРАЗМ ВОҲАСИДАГИ ТАЪЛИМ ВА МАЪРИФАТПАРВАРЛИК - Турганов, Б.К.; Мадреймов, Ф.М. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of education of highly-developed generation on the territory of Great Turan, that are considered to be an important means of the development of the society.
Keywords: Khorezm; middle ages; education; intellectuality; spirituality; school; madrasah; the generation of the Anushtakins’; mudarris; imom; religious sciences; world sciences; waphkh’s property; tourists; authors